2017
DOI: 10.1136/bcr-2017-219437
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic schistosomiasis: playing hide-and-seek with an elusive parasite

Abstract: A 27-year-old man of Eritrean origin presented with persistent left-sided abdominal pain. Initial investigation showed signs of liver fibrosis, portal hypertension and splenomegaly. A diagnosis of hepatosplenic schistosomiasis was suspected on grounds of elevated total IgE, grey area antischistosomiasis antibodies and the high endemic status of his native country. However, repeated microscopy of faecal and urine samples, as well as rectal biopsies, failed to demonstrate schistosomal eggs. Finally, the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In contrast to cirrhosis, in hepatosplenic schistosomiasis, hepatic function is preserved overall [45]. Several studies have demonstrated a correlation between disease severity (measured by i.e., organomegaly) and quantitative fecal egg output [47]. Hematochemical alterations, such as thrombocytopenia and leukopenia, classically attributed to "hypersplenism," might be due to intrasplenic blood stasis rather than sequestration with abnormal splenic function.…”
Section: Hepatosplenic Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to cirrhosis, in hepatosplenic schistosomiasis, hepatic function is preserved overall [45]. Several studies have demonstrated a correlation between disease severity (measured by i.e., organomegaly) and quantitative fecal egg output [47]. Hematochemical alterations, such as thrombocytopenia and leukopenia, classically attributed to "hypersplenism," might be due to intrasplenic blood stasis rather than sequestration with abnormal splenic function.…”
Section: Hepatosplenic Schistosomiasismentioning
confidence: 99%
“…In contrast to cirrhosis, in hepatosplenic schistosomiasis, hepatic function is preserved overall [ 45 ]. Several studies have demonstrated a correlation between disease severity (measured by i.e., organomegaly) and quantitative fecal egg output [ 47 ].…”
Section: Hepatosplenic Schistosomiasismentioning
confidence: 99%
“…Micronutrient deficiency, including B12 and folate deficiency as observed in our patient, has been observed in chronic schistosomiasis, presumably from malabsorption and reduced dietary intake due to poor appetite. 4,5 Presence of dacrocytes is usually suggestive of a myelophthisic process, which is rare but has previously been identified in the bone marrow of a patient with schistosomiasis. 6 However, our patient's bone marrow pathology was non-specific and did not demonstrate findings characteristic of a myelophthisic process including fibrosis or infiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the patient's bleeding was attributed to chronic intestinal schistosomiasis. Of note, while stool microscopy is generally considered the gold standard for diagnosing schistosomiasis, rectal biopsies actually have higher diagnostic sensitivity 4 . Rectal biopsies are particularly useful when there is a high clinical suspicion for schistosomiasis despite negative laboratory‐based testing.…”
Section: Case History/examinationmentioning
confidence: 99%
“…Detection of varices with non-invasive capsule endoscopy -Capsule endoscopy involving transit of an ingestible wireless camera along the digestive tract can be performed to visualise the entire small bowel when simultaneous therapeutic intervention or tissue sampling is not required. Capsule endoscopy has been successfully used in a pilot study to detect oesophageal varices in HSS and enabled the identification of small bowel lesions in PH together with edema, erosions and scarred mucosa [67,68]. Although clinically significant esophageal and rectal varices are typically visible endoscopically, ectopic varices may require cross sectional or multiplanar portal venous phase CT or MRI for diagnosis.…”
Section: Assessment Of Vascular Damagementioning
confidence: 99%